2021
DOI: 10.1111/bjh.17918
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the BNT162b2 mRNA COVID‐19 vaccine in haematopoietic stem cell transplantation recipients

Abstract: Summary The immunogenicity and safety of Pfizer‐BioNTech BNT162b2 mRNA vaccine in allogeneic haematopoietic stem cell transplantation (HSCT) recipients are unknown. We prospectively followed 152 HSCT recipients who were at least six months following transplantation and with no active acute graft‐ versus ‐host disease (GVHD). Blood samples were taken 2–4 weeks after the second vaccination and analyzed for receptor‐binding domain (RBD) antibodies and neutralizing antibodies (NA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
83
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 24 publications
(58 reference statements)
12
83
1
1
Order By: Relevance
“…However, 76% of patients obtained sufficient immunogenicity. Recent studies have reported that seroconversion after two doses of vaccination reaches 75-86% in allogeneic HSCT patients [7,12,[15][16][17][18]; our present results are consistent with this level. In one previous report, the main factor influencing vaccination response was the time elapsed from HSCT, with lower responses occurring within one year of HSCT [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, 76% of patients obtained sufficient immunogenicity. Recent studies have reported that seroconversion after two doses of vaccination reaches 75-86% in allogeneic HSCT patients [7,12,[15][16][17][18]; our present results are consistent with this level. In one previous report, the main factor influencing vaccination response was the time elapsed from HSCT, with lower responses occurring within one year of HSCT [15].…”
Section: Discussionsupporting
confidence: 92%
“…In our present subjects, one of the four patients vaccinated within one year from transplantation had an apparently low antibody titer, and no association with antibody titer was seen for the interval between transplantation and first dose, possibly due to the small number of patients who underwent allogeneic stem cell transplantation within 1 year before vaccination. Immunosuppressive therapy [16][17][18] and chronic GVHD [16,18] at vaccination are reported to be associated with a low response to SARS-CoV-2 vaccination. In our cohort, only three patients had developed chronic GVHD and were taking steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 82 studies were included for meta-analysis ( table 1 , supplementary table 2). 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, all studies conclude worse response in case of early vaccination, especially when initiated before 12 months post-HSCT (OR = 5.72; p = 0.048) [ 50 ]. This was also seen in the available response rates for COVID vaccination: 37–50% <12 months post-HSCT [ 48 , 56 ] versus 68–94% >12 months post-HSCT [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. One study reported on vaccination < 6 months post-HSCT with only 12.5% response ( n = 8) [ 57 ].…”
Section: Resultsmentioning
confidence: 87%
“…Only 1 article was included through snowballing. This resulted in 10 articles being suitable for this analysis, which are shown in Table 3 in order of timing of the vaccination post-HSCT [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%